Sharia Compliance in the Development of Islamic Micro Finance as a Economic Sustainability - Santika, Ana (Journal of Islamic Economics and Philanthropy, 2024)
As a microfinance institution, BMT Assyafi'iyah Berkah Nasional Lampung sometimes faces limitations in operational and investment capital, which affects their ability to expand services and help more members. Many community members, especially in rural areas, do not understand the concept of sharia finance and the benefits of using BMT services, which hinders member growth. The purpose of this study was to determine how the Implementation of Sharia Compliance affects the sustainability of the Baitul Mal Wa Tamwil (BMT) Assyafi'iyah Berkah Nasional Lampung program in poverty alleviation efforts. This study used a qualitative method using triangulation techniques to test the validity of the data. The results of this study found that Murabahah activities carried out by BMT Assyafi'iyah Berkah Nasional in Lampung have a significant impact on poverty alleviation with the management of trustworthy loan funds. Through the distribution of zakat funds, the community is helped in building their businesses. Zakat funds that are managed well can be used to provide business capital to mustahik and are beneficial. Thus, zakat and murabahah play an important role in supporting BMT to carry out its function as an institution that helps empower the people's economy and improve economic sustainability and community welfare.